Systematic elucidation of the mechanism of geraniol via network pharmacology - Zhang YF; Huang Y; Ni YH; Xu ZM (Dove Medical Press, 2019)
Yun-Fei Zhang,* Yue Huang,* Yi-Hua Ni, Zheng-Min Xu Department of Otolaryngology-Head and Neck Surgery, Children’s Hospital of Fudan University, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: Geraniol is an acyclic monoterpene alcohol, which is extracted from the ethereal oils of aromatic plants. A systematic analysis of its mechanism of action has not yet been carried out. Methods: In this study, the druggability of geraniol was assessed via Traditional Chinese Medicine Systems Pharmacology Database (TCMSP), and the potential targets of geraniol were identified using the Comparative Toxicogenomics Database (CTD). Additionally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed using WebGestalt. Drug-target-pathway networks were constructed using Cytoscape to give a visual view. Results: Our findings showed that geraniol has superb druggability with 38 putative identified target genes. GO, KEGG, and network analyses revealed that these targets were associated with cancer, inflammatory immunoreactions, and other physiological processes. Conclusion: Geraniol is predicted to target multiple proteins and pathways that shape a network which can exert systematic pharmacological effects. Keywords: geraniol, druggability, target prediction, enrichment analysis, network pharmacology